Discover the Driving Forces behind Purchase Intention in Indonesia’s Beauty Industry - Affiana Aulia; Theresia Omiwa Oktariani (TIJAB (The International Journal of Applied Business))
Background: The beauty sector is expanding significantly in Indonesia. As Indonesia's domestic beauty sector grows, consumers must select goods that meet their demands and are licensed by Indonesian Food and Drug Authority (BPOM). It is crucial for beauty sector companies in Indonesia to identify the drivers that influence consumer intention to purchase beauty products.